A survey of barriers and facilitators to primary care staff conducting research - Zoe Edwards; Michael Tatterton (PLoS ONE, 2025)
Background Research is essential to find ways of improving healthcare although is not established in primary care. This study aims to investigate the barriers and facilitators to primary care staff conducting research in one geographical area of the UK. Method A survey was developed for primary care staff using validated questions where possible. It was distributed using Online Surveys TM by email, social media and personal contact. Results One hundred and ten participants were recruited from 29 GP practices in one geographical area, 74 (67.2%) were female and 35 (31.8%) were male. Nearly three quarters (73.6%) were clinical with the remainder non-clinical staff. Sixty percent of participants had been asked to conduct research and just over 40% had never conducted research. Twenty-three participants (20.9%) had conducted research six or more times. The largest facilitator for research was the knowledge that it would make a difference to patients. Allocated time, clear communication about what was involved and making a difference for colleagues were also ranked highly. The largest barrier for research was the inability to fit anything extra in and concerns over how much work would be involved. Thirty-nine percent of clinicians knew how to gain knowledge from evidence and apply it to practice. Those who were enrolled on an educational course were more likely to be research active. Conclusion Primary care staff are more likely to take part in research if it has clear patient benefit. Communication about time commitments, research outcomes and data security are important when deciding to become involved. Staff may worry that they do not have the right skills to take part. Recommendations include co-design of studies, improved communication and administrative support. The recording of research activity and literacy at clinician annual review would allow these parameters to be measured.